2017
DOI: 10.3892/etm.2017.5580
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potentially relevant genes for myocardial infarction using RNA sequencing data analysis

Abstract: Myocardial infarction (MI) is a heart disease with high morbidity and mortality rates, thus it is critical to identify genes that serve roles during its pathogenesis. The objective of the present study was to identify potentially relevant genes during the progression of the disease. Blood samples from patients with MI and normal controls (n=3/group) were obtained, the RNA was extracted and cDNA libraries were established. RNA sequencing (RNA-seq) was performed on a HiSeq 2500 platform and fragments per kilobas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The present study confirmed rora downregulation in the serum of patients with aMi and hypoxia-treated ac16 cells, indicating a potential role of rora in myocardial anoxia. Moreover, rora, along with seven other genes, has been identified as a key gene in myocardial infarction, according to rna sequencing data (41). He et al (20) identified the protective role of RORA in myocardial i/r injury, and proposed that rora was downregulated in a mouse heart following I/R.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed rora downregulation in the serum of patients with aMi and hypoxia-treated ac16 cells, indicating a potential role of rora in myocardial anoxia. Moreover, rora, along with seven other genes, has been identified as a key gene in myocardial infarction, according to rna sequencing data (41). He et al (20) identified the protective role of RORA in myocardial i/r injury, and proposed that rora was downregulated in a mouse heart following I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study based on transcriptional profile analysis showed that upregulated IFIT3 expression was observed in human ischemic cardiac hypertrophy and MI animal models [ 11 ]. Furthermore, RNA sequencing using blood samples from patients with MI and normal controls showed that IFIT3 was upregulated in the MI patients and might be potentially relevant to the pathology of MI [ 12 ]. However, the function of IFIT3 in MI has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to loss of cardiomyocytes, left ventricular remodeling, decreased cardiac function, and potentially heart failure. MI is associated with a variety of factors, including gender, age, smoking, hypertension, and diabetes complications [2]. Microarray analysis is a widely used strategy for detecting novel biomarkers for diagnosis, prediction of disease severity, and identification of new drug targets [3].…”
Section: Introductionmentioning
confidence: 99%